An exceptional March 1912 blizzard (the Final Blizzard) that sealed the fate of Captain Scott and his party - Mila Zinkova (Arctic, Antarctic, and Alpine Research, 2025)
In March 1912, Captain Robert Falcon Scott and his remaining companions perished in a blizzard on the Ross Ice Shelf on their return journey from the South Pole. This Final Blizzard lasted nine days and was an unusual phenomenon with no analogues in recent historical data. In this study we will discuss the weather conditions that made this blizzard possible.